2012
DOI: 10.5194/hess-16-423-2012
|View full text |Cite
|
Sign up to set email alerts
|

Comparing soil moisture retrievals from SMOS and ASCAT over France

Abstract: Abstract. The first products derived over France in 2010 from the L-band brightness temperatures (T b ) measured by the SMOS (Soil Moisture and Ocean Salinity) satellite, launched in November 2009, were compared with the surface soil moisture (SSM) estimates produced by the C-band Advanced Scatterometer, ASCAT, launched in 2006 on board METOP-A. SMOS and ASCAT SSM products were compared with the simulations of the ISBA-A-gs model and with in situ measurements from the SMOSMANIA network, including 21 stations l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 78 publications
(64 reference statements)
1
43
1
Order By: Relevance
“…The soil moisture dataset is available online at http://www.ipf.tuwien.ac.at/insitu/. The observations from this network were extensively used for the validation of modelled and satellite-derived soil moisture (Albergel et al, 2008(Albergel et al, , 2010Parrens et al, 2012).…”
Section: Smosmania Stationsmentioning
confidence: 99%
“…The soil moisture dataset is available online at http://www.ipf.tuwien.ac.at/insitu/. The observations from this network were extensively used for the validation of modelled and satellite-derived soil moisture (Albergel et al, 2008(Albergel et al, , 2010Parrens et al, 2012).…”
Section: Smosmania Stationsmentioning
confidence: 99%
“…Previous studies found differences between the spatial structures of modelled and retrieved SSM (Parrens et al, 2012;Polcher et al, 2016). This paper shows that these structures are not consistent also when comparing modelled and observed TBs.…”
Section: Discussionmentioning
confidence: 49%
“…After the rotations, the vertical and horizontal polarised brightness temperatures are averaged into 10 • bins that are centred around the designated angle to enable an incidence angle based analysis. A similar approach was chosen by Parrens et al (2012).…”
Section: Smos Datamentioning
confidence: 99%
“…Examples are Albergel et al (2011), Montzka et al (2011), Parrens et al (2012 and Bircher et al (2012). Albergel et al (2011) and Parrens et al (2012) have shown that there is still potential to improve soil moisture retrievals from SMOS brightness temperatures in southern France. They used calibrated statistical relationships based on reference soil moisture values and additional information like leaf area index (LAI) simulated by a land surface model to produce better soil moisture estimates.…”
Section: F Schlenz Et Al: Analysis Of Smos Brightness Temperature Amentioning
confidence: 99%
See 1 more Smart Citation